Design and Build Omotenashi (Japanese-Style Hospitality) Applications Through Chanoyu Based on Graphical Users Interfaces (GUI) - Teti Indriati Kastuti; Sri Wulandari; Christine Dian Permata Sari (Universitas Teknologi Yogyakarta, 2023)
Along with answering the challenges of the tourism industry, which is increasingly intensifying with information technology, this study seeks to convey omotenashi knowledge using information technology in the form of digital applications. This application was developed using the R&D method and the ADDIE learning model, combining thinking skills, ethics, and activities. This type of digital application approach uses a Graphical User Interface (GUI). The purpose of this study is to create an application that provides information about 1) Knowledge of the philosophical values contained in chanoyu; 2) Knowledge of the equipment used; 3) Knowledge of the process of serving tea; 4) Knowledge of cha kaiseki (Japanese table manners); 5) Knowledge of how to deal with guests in good Japanese style. Through the interfaces of the omotenashi application, Japanese and tourism learners will more easily understand the chanoyu philosophy and the stages of the procedure that usually require a teacher in every move. With this application, the problem can be solved by following these standards, students can practice independently to get omotenashi scores and apply them in life.